Non-invasive imaging of liquid/gas flow using ultrasonic transmission-mode tomography [electronic resource] - 241220 Lee, Chin Yeow (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2008